Assessment of early-stage technology development of polyvinyl pyrrolidone-carrageenan hydrogel wound dressing - Ciocson, Gregory; Posadas, Roger (Quezon City University of the Philippines Diliman, 2014)
In 1997, the concept for the research utilizing carrageenan was conceived. A group of polymer scientists from the Ateneo de Manila University, University of the Philippines-Diliman, and De La Salle University met at the Philippine Nuclear Research Institute (PNRI) to discuss synergistic research activities on either of two major Philippine products : coconut or carrageenan. The consensus was to pursue research on carrageenan. The aspect of the research work to be contributed by the PNRI was radiation chemistry and radiation processing of carrageenan for health applications, such as hydrogel burn and wound dressings, or other environmental applications. PNRI subsequently formed a research project team. Funding was obtained from the Philippine Council for Advanced Science and Technology Research and Development (PCASTRD), an agency of the Department of Science and Technology (DOST). Funding support for the research work on the PVP-carrageenan hydrogel came from the budget of the Philippine Nuclear Research Institute, and assistance from the Department of Science and Technology. Assistance in kind such as training courses, on-the-job training, provision of consultants/experts, benchmarking with other countries in the region through meetings and workshops, came from the International Atomic Energy Agency (IAEA), the Regional Cooperative Agreement (RCA), and the Forum for Nuclear Cooperation in Asia (FNCA). In 2000, a patent application was filed with Intellectual Property Office of the Philippines when the research and development was completed and prototype of the product was made available from the laboratory. By 2002, a series of clinical trials was conducted in 29 affiliated hospitals and clinics in Luzon. The conduct of the trials was done in partnership with the identified technology collaborator Biotecos, Inc. The trials came out with very promising results, which can be considered as revolutionary (See Appendix A). By 2008, the technology was finally given an intellectual property protection through a local patent granted by IPO Philippines to DOST PNRI. By 2009, the much-awaited Technology Transfer Act was promulgated as Republic Act 10055. It paved the way for the proper commercialization of government-funded and generated technologies. The first prospective adopter of this technology was its project collaborator in the conduct of clinical trials, Biotecos, Inc. Unfortunately, before the negotiation could progress into an official licensing agreement, its president met an untimely demise. Consequently, Biotecos' board of directors decided not to pursue the commercialization anymore. This paper re-affirms that the technology works and that it has a market that the technology adopter can further develop.
In partial fulfillment of the requirements in TM 299
Thesis
Keywords: Polyvinyl pyrrolidone-carrageenan hydrogel; Hydrogel composition; Carrageenan